1989
DOI: 10.1007/bf00334634
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gentamicin nephrotoxicity by chronic inhibition of angiotensin-I-converting enzyme in rat

Abstract: Perindopril, a new specific and potent inhibitor of angiotensin-I-converting enzyme, was used to evaluate the possible participation of inhibition of the renin-angiotensin system in the development of aminoglycoside-induced renal failure. Kidney function, morphology and biochemistry were evaluated at regular intervals throughout the study. Perindopril was given orally to rats at a daily dose of 2 mg/kg for 15 days prior to and during 15-day gentamicin treatment given intraperitoneally at a daily dose of 50 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One reason for these contradictory reports is the limited sensitivity of the most commonly used indicator of aminoglycoside nephrotoxicity, that is, the increase in serum creatinine. Extensive alteration of proximal tubular cells can be observed long before this parameter is modified [10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One reason for these contradictory reports is the limited sensitivity of the most commonly used indicator of aminoglycoside nephrotoxicity, that is, the increase in serum creatinine. Extensive alteration of proximal tubular cells can be observed long before this parameter is modified [10].…”
Section: Discussionmentioning
confidence: 98%
“…In rats toxic levels of gentamicin reduce serum ACE activity slightly [10]. In rat acute renal failure caused by mercuric chloride, potassium dichromate, and uranyl nitrate increased serum ACE activity significantly [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in the functional deteriorations and renal damage induced by GM was observed after the administration of captopril that leads to suppression of progression of GM nephrotoxicity; this amelioration was related to the captopril potentiality to augmented bradykinin deliberation that leads to "vasodilator" which motivates prostaglandin production, ensuring an enlargement of the intrarenal blood vessels, and leading to an amelioration in the glomerular hemodynamic and preservation of the kidney from nephrotoxicity [15,31]. On the other hand, other studies have shown that ACEI increase GM nephrotoxicity, the concurrent treatment with perindopril and GM-induced a greater renal impairment than after the administration of GM alone [32], captopril has been found to increase GM nephrotoxicity and progressively decreased the creatinine clearance in rats [33], captopril also aggravated the detrimental consequence of GM on the renal function in rats depleted of potassium [13]. Captopril was also accompanied by a reduction of creatinine clearance and a decrease in excretion of cyclic GMP in hypertensive rats [34].…”
Section: Discussionmentioning
confidence: 99%